Hubungan Diskresi dengan Kualitas Pelayanan Publik dalam Perspektif Street-Level Bureaucracy - Bambang Aditio; Aldri Finaldi; , Roberia Roberia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the relationship between administrative discretion and public service quality within the framework of street-level bureaucracy theory. In public administration practice, implementing officials are often faced with tensions between compliance with formal rules and the dynamic needs of the community. These conditions make discretion an important instrument for adjusting policies to the realities on the ground. This study uses a literature review of various studies from 2010 to 2025 to identify patterns, dynamics, and implications of the use of discretion by implementing bureaucrats. The results of the study show that discretion allows the bureaucracy to be more adaptive, empathetic, and responsive to citizens' needs. However, without strong oversight and administrative ethics, discretion can lead to bias, injustice, and opportunities for abuse of authority. Factors such as public service motivation, professional competence, organizational culture, and political pressure have a significant influence on how discretion is applied. Thus, improving the quality of public services requires a balance between administrative control and professional trust through accountability systems, ethical oversight, and adaptive but law-based policies.